The power of nominating. Mapuche children’s names as a field of dispute - Szulc, Andrea (2012)
In the province of Neuquén, civil registry staff and schoolteachers often reject the registration or use of Mapuche children’s names. At the same time, Mapuche people have been developing individual initiatives as well as collective strategies to strengthen their self-identification, cultural revitalization and demands for official acknowledgment of the particular “ontology” of Mapuche names as well as the ways of selecting and assigning them.The names of these children, as a touchstone, will enable us to recognize the different and occasionally contradictory definitions of Mapuche identity, promoted by various social actors in the province of Neuquén.We will see that through their practices Mapuche children and “others” –Mapuche adults, communities and organizations, Catholic and Evangelical churches, teachers and State officials– turn the act of nominating into one of the arenas in which Mapuche children’s identity is increasingly disputed.